2022
DOI: 10.1108/joepp-11-2021-0311
|View full text |Cite
|
Sign up to set email alerts
|

Does lack of social interaction act as a barrier to effectiveness in work from home? COVID-19 and gender

Abstract: PurposeThe COVID-19 pandemic pushed organizations across the world to suddenly adopt work from home at a mass scale to maintain business continuity. This study aims to investigate the influence of lack of social interaction in work from the home arrangement on employee work effectiveness.Design/methodology/approachThe data were analysed using the partial least square (PLS) structural equation modelling (SEM) approach, a nonparametric method based on total variance, through SmartPLS software 3.0. The data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 56 publications
(87 reference statements)
0
6
0
Order By: Relevance
“…A total of eight studies highlight the value of productive telework. According to research, telework can enhance employee performance with the proper tools, instruction, and leadership abilities [86,87,89]. However, one study indicated that while telework may boost job quality, it may also reduce job performance [93].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of eight studies highlight the value of productive telework. According to research, telework can enhance employee performance with the proper tools, instruction, and leadership abilities [86,87,89]. However, one study indicated that while telework may boost job quality, it may also reduce job performance [93].…”
Section: Discussionmentioning
confidence: 99%
“…This study also showed that telework does not interfere with communication. Additionally, Mukherjee et al [87], who focused on social connections as a productivity hurdle, discovered evidence that participating in social interactions can significantly increase job productivity. According to Kowalski and Slebarska's [88] research, lower-level managers have a significant association between telework's advantages and effectiveness, indicating a connection between lower-level managers' perceptions of the advantages of external cooperation and their efficiency.…”
Section: Telework and Productivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Industry 4.0 and the pandemic have also made organizations emphasize disruptive innovations, building an agile workforce who can take responsibility and function with autonomy (Deepa et al ., 2023). SDL supports technological innovation and creativity (Lemmetty and Collin, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…According to the global coaching study released by the International Coaching Federation in 2020, while there is visible growth in the coaching practice, the adoption rates are abysmal in most of the Eastern world, more so in Asia. Industry 4.0 and the pandemic have also made organizations emphasize disruptive innovations, building an agile workforce who can take responsibility and function with autonomy (Deepa et al, 2023). SDL supports technological innovation and creativity (Lemmetty and Collin, 2020).…”
Section: Introductionmentioning
confidence: 99%